The Hairy Bikers' Family Cookbook : Mums Know Best! - King, Si and Myers, Dave (London Weidenfeld & Nicolson, 2010)
Si and Dave undertake a nationwide search for Britain's lost recipes - those forgotten gems or secret scribbles handed down through the generations - for a landmark BBC TV series. The Bikers send out a call-to-arms for mums, daughters and their grandmothers to unlock their private recipes and share with, and learn from, other mums.
Include Color Illustration and Index
Keywords: Cooking, British -- Cooking -- Women